2018
DOI: 10.12659/pjr.899876
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Image Quality, Diagnostic Accuracy and Radiation Dose Between Flash Model and Retrospective ECG-Triggered Protocols in Dual Source Computed Tomography (DSCT) in Congenital Heart Diseases

Abstract: SummaryBackgroundDual source computed tomography (DSCT) plays an important role in the diagnosis of congenital heart diseases (CHD). However, the issue of radiation-related side effects constitutes a wide public concern. The aim of the study was to explore the differences in diagnostic accuracy, radiation dose and image quality between a prospectively ECG – triggered high – pitch spiral acquisition (flash model) and a retrospective ECG-gated protocol of DSCT used for the detection of CHD.Material/MethodsThe st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
3
1
Order By: Relevance
“…A study by Yang et al observed an ED of 2.85 ± 2.03 mSv in children 4–12 months old 22 . When compared to a paper by Wang et al (average ED of 0.45 ± 0.23 mSv), we were able to achieve half the average ED with a smaller standard deviation (0.24 ± 0.12 mSv) 23 . Nie et al had similar findings to us with a mean of 0.29 ± 0.08 mSv 24 .…”
Section: Discussioncontrasting
confidence: 57%
“…A study by Yang et al observed an ED of 2.85 ± 2.03 mSv in children 4–12 months old 22 . When compared to a paper by Wang et al (average ED of 0.45 ± 0.23 mSv), we were able to achieve half the average ED with a smaller standard deviation (0.24 ± 0.12 mSv) 23 . Nie et al had similar findings to us with a mean of 0.29 ± 0.08 mSv 24 .…”
Section: Discussioncontrasting
confidence: 57%
“…Therefore, continuous radiation exposure is performed in multiple consecutive heartbeat cycles to obtain clear images, leading to a higher radiation dose in retrospective ECG-gated spiral acquisition compared with that in prospective ECG-triggered sequential acquisition. The advantage of the retrospective ECG-gated protocol is that the image quality of the retrospective ECGgated spiral mode was better than that of the prospective ECG-triggered sequential mode (Wang et al, 2017).…”
Section: The Preparation Of Msct (1)mentioning
confidence: 99%
“…However, the image quality of DSCT is similar to prospective and retrospective ECGgated techniques, which can significantly reduce the effective dose of patients, and has important clinical value for subjects who cannot receive a high radiation dose and whose heart rate is lower than 67 bpm (Liu & Wang, 2017;Wang et al, 2017;Pache et al, 2011;Xu et al, 2010;Ünal et al, 2015).…”
Section: The Preparation Of Msct (1)mentioning
confidence: 99%
“…However, even when automated measures are in place the principal determinants of radiation dose must always be critically appraised prior to each study, including tube current, tube potential, pitch, slice collimation and scan length. [19][20][21] Besides using the scanner specific automatic technologies, imagers should focus on both reducing radiation doses and eliminating the risk of non-diagnostic studies through careful attention to technical factors (Table 2). 17,22 The highest possible pitch and table movement speed should always be used.…”
Section: Scan Protocolmentioning
confidence: 99%